Lessons from a Pilot Project in Cognitive Task Analysis: The Potential Role of Intermediates in Preclinical Teaching in Dental Education. Issue 3 (1st March 2015) - Walker, Judith; von Bergmann, HsingChi
Abstract : The purpose of this study was to explore the use of cognitive task analysis to inform the teaching of psychomotor skills and cognitive strategies in clinical tasks in dental education. Methods used were observing and videotaping an expert at one dental school thinking aloud while performing a specific preclinical task (in a simulated environment), interviewing the expert to probe deeper into his thinking processes, and applying the same procedures to analyze the performance of three second‐year dental students who had recently learned the analyzed task and who represented a spectrum of their cohort's ability to undertake the procedure. The investigators sought to understand how experts (clinical educators) and intermediates (trained students) overlapped and differed at points in the procedure that represented the highest cognitive load, known as "critical incidents." Findings from this study and previous research identified possible limitations of current clinical teaching as a result of expert blind spots. These findings coupled with the growing evidence of the effectiveness of peer teaching suggest the potential role of intermediates in helping novices learn preclinical dentistry tasks.